Utilization of The Adityawarman Museum as A Source of History Learning - Peza Pramana Putra; Azmi Fitrisia (STKIP Singkawang, 2023)
This research aims to analyze the use of the Adityawarman Museum as a source of historical learning and its obstacles. This research was carried out in Padang City, focusing on the Adityawarman Museum and SMA PGRI 4 Padang. The form of this research is descriptive qualitative with a case study strategy. Data collection was carried out by informant interviews with teachers, students and museum officials, as well as document analysis using an inventory of the Adityawarman Museum collection, syllabus and lesson plans. The results of the research show that the use of the Adityawarman Museum as a source of history learning at SMA PGRI 4 Padang is optimal because teachers are greatly helped by the learning resources from the Adityawarman Museum collection objects, while students will understand more easily and be clearer in concretizing the material in the books history lessons and foster students' enthusiasm and activeness in learning. The use of the Adityawarman Museum as a source of history learning at SMA PGRI 4 Padang was not simply implemented well. This is because there are obstacles in its implementation, namely time, funds or costs, long distance, permits and the Adityawarman Museum collection which is more dominant about Minangkabau culture.